Bisnis Startup Dalam Kompleksitas Hukum di Indonesia - Jakobus Anakletus Rahajaan; Wahid Yaurwarin (Univiversitas Dr. Djar Wattiheluw, 2022)
The purpose of this research is to examine the complexity of pilot law and encourage the authorities to monitor the urgency of pilot law in Indonesia and the country's economic development even during the Covid-19 pandemic. Start-up companies are companies that have just entered or are still under development or research to continue to find markets and develop their products. In the competitive nature of a fast-paced industry, it is important to identify the problems companies face in order to improve business performance by finding root causes and finding effective solutions. One of the problems in start up companies is the regulation that governs the company's activities. The lack of special regulations for business start-ups hampers the sustainability of companies and other impacts of business start-ups. Start ups in Indonesia have indeed shown significant growth. On the other hand, start ups in Indonesia face challenges that often lead to start up failure. One of the reasons for this failure is that start ups are in a vortex of legal complexities that do not match the characteristics of the start up itself, thus requiring a more appropriate and flexible legal structure